Cadmium sulfide nanoparticles as a novel coating for solid‐phase microextraction. Issue 8 (11th March 2015) - Wang, Licheng; Tang, Sheng; Wang, Shuai; Liang, Xiaojing; Guo, Yong
Abstract : CdS nanoparticles coated on a stainless‐steel wire for solid‐phase microextraction was prepared. Scanning electron microscopy showed that the CdS nanoparticles clustered together to form a porous structure and X‐ray diffraction confirmed that the CdS nanoparticles were the wurtzite phase. Coupled to gas chromatography with flame ionization detection, the extraction abilities of the fiber for polycyclic aromatic hydrocarbons were examined by the headspace method. The parameters of adsorption time, adsorption temperature, salt concentration, desorption time, and desorption temperature were investigated and optimized. For the method, wide linearity and low limits of detection from 5 to 15 ng/L were obtained. The relative standard deviations for single‐fiber repeatability and fiber‐to‐fiber reproducibility were less than 10.2 and 12.6%, respectively. The enrichment factors were from 1155.6 to 3905.4, showing the fiber has good extraction capacity for polycyclic aromatic hydrocarbons. Moreover, the fiber can be used more than 50 times, exhibiting good stability. The established method was also used to analyze the polycyclic aromatic hydrocarbons in two real samples, and the recoveries from 82.7 to 114.2% further proved the reliability of the method.